Predicting dynamic geotechnical parameters in near-surface coastal environment. Issue 1 (1st January 2019) - Oladotun, Adewoyin Olusegun; Oluwagbemi, Joshua Emmanuel; Lola, Akinyemi Marvel; Maxwell, Omeje; Sayo, Akinwumi
Abstract: Conduction of geotechnical survey prior construction is a non-negotiable requirement before the erection of any engineering structure so as to avoid building collapse which has been rampant in our country of late. An easier, faster and relatively cheaper approach to conducting a comprehensive geotechnical investigation for site characterization without compromise to standards was the focus of this study. Seismic refraction method; a quick, non-destructive and non-intrusive method of obtaining key subsoil geotechnical properties necessary for foundation design for proposed engineering facilities was suggested. This approach was used to generate some seismic parameters, which are very relevant to geotechnical investigation. The seismic wave velocities generated from near surface refraction method was used to determine the allowable bearing capacity, the ultimate bearing pressure, and the liquefaction potential so as to delineate the most competent layer. The seismic refraction method delineated two layers, with the result of the allowable bearing capacity ranging between 0.092 and 0.593 MPa, the ultimate bearing capacity varied from 0.369 to 2.298 MPa while the result of the liquefaction potential varied between 0.533 and 1.237. In all, it was observed that the second layer is more competent than the first layer. Furthermore, regression equations were derived for both geotechnical parameters in order to directly derive the geotechnical parameters from the compressional wave velocities. The results obtained correlated with the results of standard geotechnical investigations carried out, which implies that the competence of any site having the same geological formation could be determined using the same approach.